Rapidly progressive interstitial pneumonia associated with anti-NXP2 antibody secondary to malignancy. (2022) - Wuthithepbuncha, Nataphon; Boonsarngsuk, Viboon; Laikitmongkhon, Jakkrit; Incharoen, Pimpin; Sukkasem, Warawut
Abstract: The diagnosis of a diffuse lung disease is challenging for physicians and it requires a multidisciplinary team approach to solve this problem. Herein, we present a case of common bile duct obstruction from pancreatic ductal adenocarcinoma after biliary stent placement, which developed a rapidly progressive bilateral lung infiltration after oesophagogastroduodenoscopy. After a diagnostic evaluation based on clinical, radiographic, and pathological findings, a diagnosis of rapidly progressive interstitial pneumonia associated with anti-nuclear matrix protein (NXP) 2 antibody secondary to malignancy was made. In patients with interstitial lung disease with unclear aetiologies, autoantibodies, including antinuclear antibody and myositis-specific antibodies should be evaluated, even if there are no clinical signs of autoimmune disease. Although this is the first case report of an acute interstitial pneumonitis-associated anti-NXP2 antibody, physicians should recognise this condition as it can rapidly cause acute fulminant respiratory failure.